2024
DOI: 10.1039/d4ta01953a
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of anodic oxidation reactions on water splitting using Prussian blue analog-derived metal-(oxy)hydroxides

Baghendra Singh,
Toufik Ansari,
Neetu Verma
et al.

Abstract: Prussian blue analog (PBA)-derived Fe–Co(O)OH showed improved anodic oxidation of a series of organic and inorganic compounds without the interference from the oxygen evolution reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…In a recent study from our group, we explored a series of AORs with a MOF-based Fe-Co(O)OH active catalyst. 156 The XPS and XAS study showed that the active Fe-Co(O)OH catalyst had dominant Co 3+ and Fe 3+ species, which played a crucial role in giving excellent performance for AORs. Moreover, excellent conversion and selectivity were observed for all the AORs with industrial-level current density.…”
Section: Active Catalyst Structure Of Mofs For Aormentioning
confidence: 98%
See 4 more Smart Citations
“…In a recent study from our group, we explored a series of AORs with a MOF-based Fe-Co(O)OH active catalyst. 156 The XPS and XAS study showed that the active Fe-Co(O)OH catalyst had dominant Co 3+ and Fe 3+ species, which played a crucial role in giving excellent performance for AORs. Moreover, excellent conversion and selectivity were observed for all the AORs with industrial-level current density.…”
Section: Active Catalyst Structure Of Mofs For Aormentioning
confidence: 98%
“…Consequently, the creation of this highly stable active catalyst enhances the stability of MOFs for anodic oxidation reactions. 40,156 The following steps are involved in the electrocatalytic oxidation of organic and inorganic substrates: 72,79,131,132 the substrates' adsorption onto the active catalyst surface is the first step, followed by hydroxyl addition, electron transfer (oxidation), and deprotonation (proton decoupling). For the most part, anodic oxidation follows these common processes.…”
Section: Active Catalyst Structure Of Mofs For Aormentioning
confidence: 99%
See 3 more Smart Citations